Measures of inflation and its impact on Indian Economy - T POTE, RAMESH; S KATTI, MEDHAVINI (International Journal of Psychosocial Rehabilitation, 2024)
Inflation is one of the economic parameter to be associated with the hike of price, it has its long and far reaching effects on the society and social concerns. Inflation is a sustained increase in the general price level of goods and services in an economy over a period of time. When the price level rises, each unit of currency buys fewer goods and services. Consequently, Inflation reflects a reaction in one purchasing power per unit of money. Fluctuations in prices create an atmosphere of uncertainty which is not conducive to development activity. So inflations mean paying more for goods than paying earlier. Not only essential goods see a hike, non-essential items like cigarettes etc. would also cost more. The price of everything goes up over time. The present article made an attempt to study the impact of inflation on the economy, and measures of inflation in India. So in respect of obtaining a better view of the effects and influence of inflation on the society we need to take mainly the experience of poor and developing nations. This paper analyses the effects of inflation on our country’s economy that emerged in the recent past.